2019
DOI: 10.3390/ani9121028
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the Goat Rumen Microbiota Involves Three Stages of Microbial Colonization

Abstract: With increasing age, the rumen microbiota of new-born ruminants become central in the translation of fibrous feed substances into essential nutrients. However, the colonization process of the microbial community (especially fungal community) remains poorly understood in ruminants at pre-weaning stages. In this study, the rumen bacterial and fungal colonization processes were investigated in goats at eight stages using amplicon sequencing. For bacteria, we found 36 common core genera at D0, D3, D14, D28, and D5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…A good digestive tract microbiota benefits the host by regulation of the physiological procedure and mucosal immunity, from producing antimicrobial substances to suppressing the proliferation of digestive tract pathogens [23], leading to a highly efficient rumen function [24] and improving growth performance through improving the digestive tract microbial ecosystem [25]. In the present study, Firmicutes and Bacteroidetes were the two dominant phyla in the rumen and caecum, which is in agreement with previous studies [26,27]. Our research indicated that the Firmicutes abundance in the rumen and caecum increased after feeding weanling goats with Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09, but the Bacteroidetes abundance decreased in rumen and caecum, indicating that Bacillus amyloliquefaciens fsznc-06 and Bacillus pumilus fsznc-09 improved Firmicutes proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…A good digestive tract microbiota benefits the host by regulation of the physiological procedure and mucosal immunity, from producing antimicrobial substances to suppressing the proliferation of digestive tract pathogens [23], leading to a highly efficient rumen function [24] and improving growth performance through improving the digestive tract microbial ecosystem [25]. In the present study, Firmicutes and Bacteroidetes were the two dominant phyla in the rumen and caecum, which is in agreement with previous studies [26,27]. Our research indicated that the Firmicutes abundance in the rumen and caecum increased after feeding weanling goats with Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09, but the Bacteroidetes abundance decreased in rumen and caecum, indicating that Bacillus amyloliquefaciens fsznc-06 and Bacillus pumilus fsznc-09 improved Firmicutes proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the aminoacyl-tRNA biosynthesis pathway and the metabolic pathways of butanoate, cysteine, and methionine were more active in high finishing weight rabbits, whereas ABC transporters, and fructose, mannose, and tyrosine metabolic pathways were overrepresented in rabbits with low finishing weight ( Figure 5). The aminoacyl-tRNA biosynthesis pathway is an essential metabolic function of microorganisms and is intimately correlated with maturation of gastrointestinal microbiota (Zhang K. et al, 2019). More importantly, microbial mature status is fundamental for host development and growth (Wang X. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to the temporal characteristics of four stomachs especially with the rumen, the development of the gastrointestinal system in sheep can be divided into three temporal stages: non-rumination (0–21 days), transition (21–56 days), and rumination stages (from 56 days onward) ( Wardrop and Coombe, 1960 ; Lane et al, 2002 ). However, direct evidence from goats was limited, and recent longitudinal analyses showed that the rumen ( Jiao et al, 2015b ; Zhang et al, 2019 ) and ileal ( Jiao et al, 2016 ) microbiota in goat kids underwent dramatic changes in three stages during the first 2 months after birth. Furthermore, other studies showed that the first 2 days of life were the initial phase of the gut microbiota establishment in ruminants, according to the analyses of the ruminal microbiota and VFA concentrations in calves ( Rey et al, 2014 ) and goat kids ( Abecia et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The establishment and temporal dynamics of the healthy rumen microbiota have been well characterized in normal cattle ( Li et al, 2012 ; Jami et al, 2013 ; Rey et al, 2014 ) and goats ( Han et al, 2015 ; Jiao et al, 2015a,b ; Wang et al, 2016 ; Zhang et al, 2019 ) during different growth stages. Particularly, the initial establishment of the gut microbial community in ruminant kids after birth generally occurs in three successive stages: the initial colonization stage, the transitional stage, and the mature stage ( Buddle et al, 2011 ), according to the observations on the rumen microbiota in early life ( Li et al, 2012 ; Jami et al, 2013 ; Rey et al, 2014 ; Jiao et al, 2015b ; Zhang et al, 2019 ). However, the initial colonizers of the gut microbiota depend on the delivery mode (i.e., vaginal delivery or cesarean section), feeding-management operations, and the surrounding environments ( Arrieta et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%